Strategic Analysis of the Export Potential of Sentul Drums from Blitar: A Desk Research Approach - Bambang Septiawan; Sudarmiatin; Heri Pratikto (Kirana Publisher (KNPub), 2026)
This study aims to conduct a strategic analysis of the export potential of Sentul Drums (also known as Kendang Sentul or Kendang Jimbe) from Blitar, East Java, using a pure desk-research approach. Anchored in Porter’s competitive advantage theory and the Uppsala internationalization model, the research synthesizes secondary data from government reports (BPS, Disperindag), official regulations, credible media (Antara News, Kompas, BlitarKawentar), and peer-reviewed literature (2021–2026). Findings reveal that Kendang Jimbe has become Blitar’s leading export commodity, generating Rp17.99 billion in 2025, driven by large-scale shipments to China (3,500 units worth Rp17.6 billion via BUMDes Ngoran in 2024 and over 5,000 units via UKM Jatim in early 2025). PESTLE analysis confirms a highly supportive macro-environment, while the updated SWOT/IFAS-EFAS matrix positions the industry in a growth quadrant. The study formulates actionable SO, ST, WO, and WT strategies focusing on BUMDes collaboration, digital marketing, logistics optimization, and market diversification. This desk-based synthesis fills a literature gap by providing an objective, up-to-date roadmap for enhancing MSME export competitiveness in Indonesia’s creative economy sector.